Peran Kepemimpinan Kepala Madrasah Dalam Membentuk Prestasi Kegiatan Ekstrakulikuler Di MIN 04 Kepahiang - Iis Sugianti; Murniyanto Murniyanto; Syaiful Bahri (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research looks at the madrasa head's leadership role in shaping the achievements of extracurricular activities at Madrasah Ibtidaiyah Negeri (MIN) 04 Kepahiang. This research uses a descriptive qualitative approach. The research subjects were madrasa heads, extracurricular supervisors, curriculum assistants, and students. Data collection techniques are observation, interviews, and documentation. Data analysis techniques include data reduction processes, data presentation, and conclusions. This research found that first, the role of the madrasa head in shaping the achievements of extracurricular activities: forming the extracurricular structure, providing guidance and direction to extracurricular supervisors, planning financial budgets for extracurricular activities, always coordinating and supervising extracurricular activities, and carrying out continuous evaluation. These two processes shape the achievements of extracurricular activities at MIN 04 Kepahiang: blending all madrasa elements, developing programs together, appointing coaches and trainers, providing a budget, and preparing activity schedules; the madrasa head monitors activities; the charge of the madrasah carries out evaluations and; The madrasah coordinates with the committee and the students' parents. The three impacts of the madrasa head's leadership in shaping the achievements of extracurricular activities are: some students can continue to junior high school for free and are boarded at PPLP and SKO Bengkulu for high school; students can take part in various competitions at KSM; develop talents, interests in sports, Mathematics and Natural Sciences and recitations and; Students who excel can continue to favorite/superior schools. In conclusion, there is a leadership role for school principals so that they can improve achievement in extracurricular activities. Keywords: Extracurricular Achievement, Leadership of the Madrasah Head, Role,